GENDER CONCEPT FROM ISLAMIC EDUCATION PHILOSOPHY PERSPECTIVE - Suhari; Pong Kok Shiong (Adisam Publisher, 2023)
Equality of women and men has been a hot topic for 20 years. In general, gender is the visible difference between men and women when viewed from values and behavior. So far, gender issues have been dominated by women's perspectives, while men's perspectives have not been discussed much. The dominance of women's perspectives often results in a dead end in finding the desired solution, because it ultimately leads to problems originating from men. Islam does not differentiate between the rights and obligations that exist in human anatomy, these rights and obligations are always the same in the eyes of Islam for both different anatomies. Islam puts forward the concept of justice for anyone and everyone regardless of their gender.